KINERJA PEGAWAI NEGERI SIPIL (PNS) PADA KANTOR DINAS PERHUBUNGAN KABUPATEN MAHAKAM ULU - Petrus Bawaan Petrus Bawaan Juk (ADMINISTRASI PUBLIK, 2020)
This research aims to know and define ecological performance of Government Employees in Dinas Perhubungan Kabupaten Mahakam Ulu East Borneo District along with the factors that inhibit and support the performance of Government Employees.The results of research and interview of the performance of Bappeda Provinsi East Borneo district had been appropriate affirmed whether this can be seen from the Factors supporting the performance of Government Employees in Dinas Perhubungan Kabupaten Mahakam Ulu  district which is a sufficient infrastructure & facility and support the fluency of carrying the tasks that are given to the employees. But there is still something must be repaired because of resistance factors the performance of government employees in East Borneo district amongst other limited  Human Resources and employees undisciplined.